Mathematical model of H-polarized wave radiation from longitudinal slots of a cylindrical antenna - Girya, Nataliya Petrivna; Dukhopelnykov, Sergii Volodymyrovich (НТУ "ХПІ", 2018)
In the paper mathematical model is developed for straight perfectly conducting circular cylindrical antennas with the finite number of longitudinal slots, in the case of H-polarized wave. Boundary hyper-singular integral equations of boundary value problem for the Helmholtzequations are introduced in the case the boundary is the cylindrical surface with longitudinal slots. Using the boundary integral equation we construct the discrete mathematical model of the problem of electromagnetic waves radiation from the structure slots, also the numerical experiment is conducted. The near and far fields are plotted for different parametersof the structure.

Розглянуто циліндричну антенну структуру, яка має скінченну кількість подовжніх щілин. Розглянуто випадок випромінювання H-поляризованої хвилі. Отримано граничні гіперсингулярні та сингулярні інтегральні рівняння крайової задачі для рівняння Гельмгольця у випадку, коли границя – це циліндрична поверхня з поздовжніми щілинами. На основі граничного інтегрального рівняння побудовано дискретну математичну модель задачі випромінювання електромагнітних хвиль із щілин структури та проведено чисельний експеримент. Побудовані поля у ближній зоні та діаграми розсіяння для різних параметрів структури.
Математична модель випромінення H-поляризованої хвилі з поздовжніх щілин циліндричної антени
Keywords: circular cylindrical antenna; discrete mathematical model; hypersingular integral equation; diffraction problems; method of discrete singularity; electromagnetic waves; кругова циліндрична антена; дискретна математична модель; гіперсингулярне інтегральне рівняння; щілинна циліндрична антена; метод дискретних особливостей; електромагнітні хвилі